How Speech Acts Are Used to Achieve Political Goals in President Biden’s 2023 State of the Union Address : A Mixed Methods Study - Vuorela, Markus (My University, 2024)
Speech act theory is based on the theory that words are not only used to give information, but are also used to do actions, such as making promises, asking questions, and many other kinds of actions. This mixed methods study examines what kinds of political goals are being pursued based on the use of speech acts, and how different kinds of speech acts are utilized to achieve those goals. This thesis follows John R. Searle’s system for categorization of speech acts, which divides speech acts into five categories based on the illocutionary verb used. The different categories of speech acts according to Searle are assertives, directives, commissives, expressives, and declaratives, which can be divided further by the type of illocutionary verb used. The source material is the U.S President Joe Biden’s State of the Union Address of 2023, which has an official purpose of informing members of the congress about the state of the nation, but also serves as a way for the President to talk about topics important to him. This address specifically marks the beginning of for President Biden’s campaign for the 2024 Presidential election. The address is an opportunity for President Biden to establish his political stances on currently relevant topics and to build up an image of a competent leader, capable of leading the nation for four more years. President Biden would also need to succeed in garnering support for the remainder of this presidential term, as at the time of the address President Biden had historically low approval rates. The address uses a mixture of speech acts for a variety of purposes. Speech acts in the address are split towards two different audiences, members of the congress and the public, as different speech acts are intended only for the other. Assertives are used to inform the audience of President Biden’s political views and what kinds of accomplishments his administration has had. The general topics of the address are likely to be central in the campaign. Directives and commissives are used decisively to appeal for bipartisanship from the Republicans, by using polite forms of speech acts, which also gives the President an image of a well-mannered, rational, and reasonable politician, while making a refusal from the Republicans seem childish. Speech acts with a more serious tone are used to emphasize political messages to the public, indicating that the topics are important to President Biden and that he understands what kinds of issues Americans are currently concerned with. The address gives President Biden an image of a strong leader, who is capable of leading the nation further on, regardless of his age. This thesis is intended to supplement existing research on political speeches and of President Biden. By utilizing a less conventional theory for political speech analysis, this thesis presents a unique perspective on the use of language in politics.
Keywords: State of the Union Address, speech act theory, President Biden, John R. Searle